2018
DOI: 10.15381/rivep.v29i1.14198
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidad genética de las poblaciones de palomas domésticas (Columba livia) en Sincelejo, Sucre

Abstract: El objetivo de la presente investigación fue determinar la variabilidad genética de las poblaciones de palomas domésticas (Columba livia), utilizando genes que codifican la coloración y diseño del plumaje en Sincelejo, Sucre (Colombia). Las poblaciones, distribuidas en veinticuatro colonias, se estudiaron entre julio de 2016 y enero de 2017 e incluyeron 1402 individuos. Se evaluaron los marcadores: Patrón del plumaje, Coloración primaria, Spread y Grizzle. Los parámetros genéticos frecuencia alélica, diversida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Cuando la oferta de alimentos disminuye, las hembras con fenotipos oscuros tienen mayor producción de huevos y, por lo general, las crías tienen una mayor masa corporal (Causil et al 2016). Por el contrario, cuando abunda la comida, la producción de huevos es similar para ambos fenotipos, pero en el caso de los adultos la pérdida de masa corporal es mayor en los animales más claros (Pardo et al 2018).…”
Section: Aspectos Genéticosunclassified
“…Cuando la oferta de alimentos disminuye, las hembras con fenotipos oscuros tienen mayor producción de huevos y, por lo general, las crías tienen una mayor masa corporal (Causil et al 2016). Por el contrario, cuando abunda la comida, la producción de huevos es similar para ambos fenotipos, pero en el caso de los adultos la pérdida de masa corporal es mayor en los animales más claros (Pardo et al 2018).…”
Section: Aspectos Genéticosunclassified
“…In urban areas, domestic pigeons feed on scattered grains and seeds found on the ground. As a result, they tend to rely on humans for food, as a significant portion of their diet consists of edible waste left by humans in streets, parks, or garbage bins (Pardo et al, 2018). In their wild state, their diet is based on seeds, berries, and invertebrates, leading to some studies considering them as omnivores.…”
Section: Introductionmentioning
confidence: 99%
“…Columba livia is no exception, with 60 hereditary factors identified that encode for its plumage patterns and coloration. This extensive set of genetic factors serves as a crucial tool in population genetic studies, offering information about a large number of individuals with less effort and investment, while also enabling swift identification and characterisation (Pardo et al, 2018).…”
mentioning
confidence: 99%
“…The feral pigeon, Columba livia forma urbana (Gmelin, 1789), is one of the most numerous urban bird species in many European and American cities (Janiga, 1991;Johnston, Janiga, 1995;Saari, 1997;Obukhova, 2001Obukhova, , 2007Obukhova, , 2011Sacchi et al, 2002;Hetmański, Jarosiewicz, 2008;Ferman et al, 2010;Kowalski et al, 2011;Jacquin et al, 2010;Čanády, Mošanský, 2013Čanády, Mošanský, , 2016Vickrey et al, 2018;Pardo et al, 2018). The mentioned authors showed that large concentrations of these birds were primarily observed in old town centers, in church towers, museums, theatres, railway stations, and attics.…”
Section: Introductionmentioning
confidence: 99%